Litteratur efter orientalismen - Hafez, Sabry (Passage - Tidsskrift for litteratur og kritik, 2009)
Sabry Hafez: “Literature after Orientalism – The Enduring Lure of the Occident: Modernity, Canon and Translatability” After reflecting on the status and challenge of “world literature”, the article addresses three issues concerning orientalism: modernity, canon and translatability. The attraction to the West played a significant role in the formation of the modern Arabic literary canon, despite Arabic culture’s long history and tradition of creating its own canon. Unlike the West, in which the concepts of canon and canonical literary texts goes only to the 18th century, Arabic culture has had its classics and classification of writers and works since pre-Islamic time and the idea of Mu’allaqat, when a few poems were selected to be hung on the walls of the Ka‘bah. The concept of classics, and the formation of the literary canon in the modern period, benefitted from some of the achievements of the past, but had its eyes on the occident, which was clearly in the desire to have works recognised by the West, first by its specialists, read orientalists, then by its literary circles. The intervention of the international literary field led to a crisis of canon and a distortion of the literary field in Arabic culture, which was already distorted by the intervention of the establishment. Finally, the article considers the marginal role Arabic literature plays in world literature today.